"Healthcare as a refuge": building a culture of care in Montreal for refugees and asylum-seekers living with HIV. Issue 1 (11th March 2019) - Robert, Emilie; David, Pierre-Marie
Abstract : Purpose: Between 2012 and 2016, the Government of Canada modified health insurance for refugees and asylum seekers. In Quebec, this resulted in refusals of care and uncertainties about publicly reimbursed services, despite guaranteed coverage for people with this status under the provincial plan. The Chronic Viral Illness Service (CVIS) at the McGill University Health Centre in Montreal continued to provide care to refugees and asylum seekers living with HIV. The purpose of this paper is to explain how and why challenges brought by this policy change could be overcome. Design/methodology/approach: A qualitative case study was conducted using interviews with patients and staff members, observation sessions and a review of media, documents and articles. A discussion group validated the interpretation of preliminary results. Findings: The CVIS provides patient-centered care through a multidisciplinary team. It collectively responds to medical, social and legal issues specific to refugees. Its organizational culture and expertise explain the sustained provision of care. The team's empathetic view of patients, anchored in the service's history, care for men who have sex with men and commitment to human rights, is key. A culture of care developed over time thanks to the commitment of exemplary figures. Because they countered the team's values, changes in refugee healthcare coverage strengthened the service's culture of care. However, the healthcare system reform launched in 2014 in Quebec is perceived as jeopardizing the culture of care, as it makes, refugee and asylum-seeker patients a non-lucrative venture for providers. Originality/value: This research analyzes the origin of sustained provision of care to refugees and asylum seekers living with HIV through the lens of culture of care. It considers the historical and political contexts in which this culture developed.